The value of information in a cooperative environment - Galdeano, Patricia; Oviedo, Jorge; Quintas, Luis Guillermo (Estudios de Economía, 2016)
In this paper we analyze the value of the information in a cooperative game.There is a player, the innovator, having a know how or relevant informationwhich is not useful for himself but it can be sold to some potential buyers. The npotential users of the information are involved in a market having all them thesame characteristics. The expected utility of each of them can be improved byobtaining the information. The whole situation is modeled as a (n + 1)–persongame. The Shapley Value is the cooperative solution studied.We deal with a game in characteristic form function, where this function can benon-superaditive. Supearditivity have been a usual assumption in cooperativegames, but we show that under a weak version of superaditivity it is still possibleto use the Shapley Value as a cooperative solution. We give conditions forthe weak superaditivity and study the implications of those conditions on theresulting market.We also compare the Shapley Value with the outcomes obtained in a noncooperativeapproach by Quintas (1995). Finally we arrive to the conclusion thatthe innovator prefers the noncooperative outcome and the users prefer the cooperativeoutcomes.